Functional Groups of Scale Collagen from Farmed Snakehead Fish (Channa striata) and Wild Sources - Ayu Agustina; Bustari Hasan; Mery Sukmiwati (Jurnal Perikanan dan Kelautan, 2023)
The study aimed to analyze the functional groups of scale collagen from farmed snakehead fish and wild sources. Scale collagen from farmed snakehead fish was higher than the wild sources (18.82 > 14.27%) with the protein content of both successively (60.24 > 59.78%). The functional groups in scale collagen from farmed snakehead fish were Amide A (3668,77 cm-1), Amide B (2920,35 cm-1) Amide I (2302,14 cm-1), Amide II (1446,67 cm-1), and Amide III (1245,10 cm-1). Meanwhile, scale collagen from wild sources snakehead fish has an Amide A group (3853.94 cm-1), Amide B (2905.89 cm-1), and Amide I (1869.10 cm-1) Amide II (1457.28 cm-1), Amide III (1243.18 cm-1). Scale Collagen from farmed snakehead fish and wild sources is classified as type 1 collagen